The metabolic and analytical changes of healthy volunteers upon intake of Portuguese extra virgin olive oil: a comparison study between pre- and post-intervention - Correia, Marta (2023)
(1) Background: Extra virgin olive oil (EVOO) is studied mostly for its health benefits in preventing non-communicable chronic diseases, particularly within a Mediterranean dietary pattern. However, few studies have addressed the effect of EVOO in healthy individuals, prior to an established disease. This study aims to evaluate the impact of Northern Portuguese polyphenol-rich EVOO (NPPR-EVOO) consumption on various important clinical parameters in healthy adult volunteers. (2) Methods: This quasi-experimental intervention study assessed the impact of NPPR-EVOO for a period of 100 days. Serum total cholesterol, HbA1c, HDL-c, LDL-c, and CRP, and anthropometric measures—waist and hip perimeters, hand grip strength, and body fat—were assessed and food logs were analyzed. (3) Results: Serum HbA1c (5.12 ± 0.32%; 4.93 ± 0.24, p = 0.000) and LDL-c (96.50 ± 28.57 mg/dL; 87.41 ± 31.38 mg/dL, p = 0.017) significantly decreased following NPPR-EVOO. Also, daily energy significantly increased, but no changes in other dietary parameters, or anthropometry, were seen. Adherence to the Mediterranean diet did not explain the differences found in individuals regarding serum lipid profile and HbA1c, reinforcing the role of EVOO’s effect. (4) Conclusions: NPPR-EVOO lowered the serum levels of LDL cholesterol and HbA1c, providing clues on the effect of EVOO-putative health benefits. These results pave the way for a deeper exploration of EVOO as a functional food.